Enhancing Motivation for Oral Hygiene Implementation among Immobilized Compos Mentis Patients through The Development of a Dental Care Table in Inpatients Settings - Mokhamad Ainu Roziq; Sukini Sukini; Diyah Fatmasari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Brushing teeth is one way to maintain oral hygiene. Implementation of tooth brushing with oral hygiene protocols in hospitalized patients in addition to avoiding infection can also improve the quality of life of patients during treatment. There are often cases of neglected oral hygiene in hospitalized patients. This is due to the limitation of movement (immobilization) in patients to carry out these activities. Often the appearance of discomfort when using supporting infrastructure in the room such as basins. Dental care table (DCT) is an idea in supporting the implementation of oral hygiene while in bed. Interest in the latest innovations is expected to encourage the motivation of immobilized patients with compost mentis to carry out oral hygiene activities that have been carried out at home. This study aims to determine the description of the motivation for implementing oral hygiene for immobilized patients with kompos mentis in the inpatient installation . This type of research with Research and Development (R&D) and pre-experiment research (Pretest and Posttest group design) with purposive sampling technique obtained 32 respondents. The method of measuring product feasibility uses David Garvin's